Dry batch and semi-continuous digestion: optimising the science behind it - Rocamora Miguel, Ildefonso (Cranfield University, 2022)
Dry anaerobic digestion (AD) is usually linked to inhibitors accumulation, however existing knowledge from wet AD cannot be directly translated to palliate this issue due to the high total solids content (TS) and the reduced mixing limiting diffusion and free water where reactions take place. This thesis investigated the main inhibitory pathways in dry AD and the effect of operational parameters on them. In batch processes the adjustment of the inoculum to substrate ratio (I:S) demonstrated an effect on reducing acidification at the beginning of the process. Furthermore, percolate recirculation showed the best impact to improve contact between microorganisms and substrate and buffer the digester, avoiding pH reduction and producing an 8-fold increase in total methane production compared to water addition at similar conditions. Optimisation of percolate recirculation was also key in maximising production of methane in the full-scale batch dry AD plant studied, with drops of production if recirculation was over the optimum range due to collapse of the biomass pile and inhibitors accumulation. Semi-continuous dry AD of organic fraction of municipal solid waste (OFMSW) resulted in high ammonia accumulation, followed by accumulation of propionic acid producing reactor failure. Different dosing strategies were tested when digesting OFMSW. Dose of trace elements (TE) was done to improve synthesis of enzymes needed in hydrogenotrophic methanogenesis, activated carbon (AC) was added to increase electron transfer between hydrogenotrophic archaea and syntrophic bacteria, while MgCl2 aimed to maintain intracellular osmotic pressure and reduce free ammonia (FA) inhibition. TE dosing increased methane production but did not avoid the accumulation of propionic acid. These results were contrary to available literature in AD at TS lower than 20 %, probably due to the reduced diffusion observed at 40 % TS. Addition of AC and an osmoprotectant like MgCl2 were also unable to reduce propionic accumulation, but methane production improved by 28 % compared to the TE additions. Additionally, short retention times where insufficient for syntrophic acetate oxidation bacteria (SAOB) due to inhibition, producing its wash followed by the reduction of strict hydrogenotrophic archaea. This allowed versatile Methanosarcina to become dominant and change methane production to acetoclastic even at high FA over 1 g/l.
Wagland, Stuart T. - Associate Supervisor
Keywords: Dry anaerobic digestion; operational parameters; organic fraction of the municipal solid waste; percolate recirculation; inhibition; ammonia; propionic acid accumulation; syntrophic acetogenic oxidation; butyric accumulation; osmoprotectants; trace elements; activated carbon.